Application of vascularized perforant flaps in the hand restoration in electro-thermic affections - A. O. Zhernov; O. M. Kovalenko; O. A. Zhernov (Клінічна хірургія, 2020)
Objective. To improve the results of surgical treatment in patients with deep electric burns of the hand, using local vascularized flaps, based on perforant vessels.